Fabrication and characterization of porous, conductive, monolithic Ti4O7 electrodes. (10th February 2018) - Nayak, Sasmita; Chaplin, Brian P.
Abstract: Highly porous and conductive monolithic electrodes have found various electrochemical applications in water treatment and energy storage and conversion. In this work we have successfully synthesized monolithic Ti4 O7 electrodes by two production methods—mechanical pressing of Ti4 O7 powders and gel casting of TiO2 powders followed by sintering and reduction to Ti4 O7 . The electrodes were characterized by X-ray diffraction (XRD), Hg porosimetry, scanning electron microscopy, thermal gravimetric analysis, Mott-Schottky analysis, and sweep voltammetry. The removal of oxygen atoms from the TiO2 precursor resulted in n-type doping behavior, and XRD measurements confirmed the electrodes consisted of high purity Ti4 O7 . Porosimetry analyses indicated the electrodes had high porosities (44–48%) and low bulk densities (∼2.0 g cm −3 ), which allowed for high permeate fluxes of up to 801 ± 81 LMH bar −1, when operated in a flow-through mode. The efficient mass transfer achieved in the porous electrodes resulted in high rate constants for the oxidation of Fe(CN)6 4− ( k obs  = 3.0–4.5 × 10 −4  m s −1 ). The electrodes also showed high rates of removal for oxalic acid and terephthalic acid, which were probes for direct oxidation and OH production, respectively. Chemical etching of the electrodes increased the electroactive surface area by approximately 2-fold, which increased the capacitance (30 mF cm −2 ) and reactivity of the electrodes towards outer sphere electron transfer reactions and the production of OH by the same factor. These results indicated that the Ti4 O7 monolithic electrodes could enhance charge transfer reactions in various electrochemical applications. Graphical abstract: